2014
DOI: 10.1063/1.4884962
|View full text |Cite|
|
Sign up to set email alerts
|

An exploration of the ozone dimer potential energy surface

Abstract: Articles you may be interested inThe (O 3 ) 2 dimer potential energy surface is thoroughly explored at the ab initio CCSD(T) computational level. Five minima are characterized with binding energies between 0.35 and 2.24 kcal/mol. The most stable may be characterized as slipped parallel, with the two O 3 monomers situated in parallel planes. Partitioning of the interaction energy points to dispersion and exchange as the prime contributors to the stability, with varying contributions from electrostatic energy, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
6
1
Order By: Relevance
“…Dissociation energies for the C i and Cs-B inplane structures obtained by Azofra et al [24] and Gadziev et al [25] are much larger than found here. It appears that in both cases BSSE corrections were not applied.…”
Section: Structures and Dissociation Energies For Complexes Of Ozone ...contrasting
confidence: 58%
“…Dissociation energies for the C i and Cs-B inplane structures obtained by Azofra et al [24] and Gadziev et al [25] are much larger than found here. It appears that in both cases BSSE corrections were not applied.…”
Section: Structures and Dissociation Energies For Complexes Of Ozone ...contrasting
confidence: 58%
“…The same sort of tetrel bonding through a C π-hole occurs in other systems as well [ 32 , 33 ]. This idea is not restricted to C but occurs on other sorts of atoms—for example, the S atom of SO 2 [ 31 ] or SO 3 [ 34 ] or the central O of ozone [ 35 ] or for tetrel T atoms larger than C, as in F 2 TO [ 36 , 37 , 38 ], or the N atom of the -NO 2 group [ 39 ]. Other planar examples involve triel (Tr) atoms in TrR 3 , where R indicates some substituent [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…The recent development of the concept of chalcogen bond [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] leads naturally to the need to explore the importance of such bonds that involve CO 2 . Also relevant are the recent findings that the C atom can participate in fairly strong noncovalent bonds, commonly referred to as tetrel bonds.…”
Section: Introductionmentioning
confidence: 99%